2014
DOI: 10.1007/s12471-014-0594-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular ejection fraction in patients eligible for ICD therapy: Discrepancy between cardiac magnetic resonance imaging and 2D echocardiography

Abstract: ObjectiveImplantable cardioverter defibrillators (ICD) and cardiac resynchronisation therapy (CRT) have substantially improved the survival of patients with cardiomyopathy. Eligibility for this therapy requires a left ventricular ejection fraction (LVEF) <35 %. This is largely based on studies using echocardiography. Cardiac magnetic resonance imaging (CMR) is increasingly utilised for LVEF assessment, but several studies have shown differences between LVEF assessed by CMR and echocardiography. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…Echocardiography is the single most commonly used diagnostic test in the evaluation LVEF in patients with heart failure. Most previous studies reported an overestimation of LVEF by non‐contrast echocardiography compared with CMR, and this discrepancy increased with larger LV volumes and lower LVEF . There was no significant difference in LVEF between the two imaging modalities in our study which could be explained by the fact that only 35% of the patients had severely reduced LVEF.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Echocardiography is the single most commonly used diagnostic test in the evaluation LVEF in patients with heart failure. Most previous studies reported an overestimation of LVEF by non‐contrast echocardiography compared with CMR, and this discrepancy increased with larger LV volumes and lower LVEF . There was no significant difference in LVEF between the two imaging modalities in our study which could be explained by the fact that only 35% of the patients had severely reduced LVEF.…”
Section: Discussioncontrasting
confidence: 55%
“…The use of CMR may affect cardiac device eligibility in particular in patients with borderline LVEF that is ±5% within the cutoff value. Previous studies comparing non‐contrast echocardiography and CMR demonstrated that use of CMR led to reclassification for cardiac device eligibility in up to 41% of the patients . The present study showed that only 1 (6%) patient with optimal images on non‐contrast echocardiography was reclassified for device eligibility by CMR.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…22,23 CMR imaging is a standardized technique that, thanks to high spatial resolution and independence from geometric assumptions, represents the reference standard for LV volumes and LVEF measurement. 24,25 Indeed, a significant discrepancy between CMR and TTE has been demonstrated, ranging from 7% LVEF overestimation to 4% underestimation with the latter imaging technique 26,27 with the majority of studies indicating an overestimation of LVEF assessment by TTE. 21 In addition, CMR has proven to have high diagnostic and prognostic value in cardiomyopathy evaluation apart from the pure LVEF estimation, thanks to LGE technique.…”
Section: Discussionmentioning
confidence: 99%
“…However LVEF assessed by cardiovascular magnetic resonance imaging (CMR) is significantly lower compared with echocardiography [14]. Therefore CMR would significantly increase the number of CHF patients eligible for CRT or ICD implantation.…”
Section: Introductionmentioning
confidence: 99%